Donor-Derived Urothelial Carcinoma in Renal Transplant Recipients - Zhiyu Qian; Emily Chou; Jing Yang; Hanwei Zhang; HuiHui Ye; Sandy T. Liu; Arnold I. Chin (Case Reports in Urology)
Cancer is a significant cause of morbidity and mortality in recipients of renal transplantation. The vast majority develop from recipient origins, whereas donor-derived malignancies are exceedingly rare. We report 2 cases of poorly differentiated donor-derived urothelial carcinoma (UC) in renal transplantation recipients. The first patient underwent a living-related-donor renal transplantation 24 years prior and presented with back pain, hematuria, and rising creatinine and was found to have a 14 cm mass in the renal allograft with regional lymphadenopathy and liver metastases. Pathology showed UC with small-cell differentiation. The second patient presented with hematuria and rising creatinine and was initially found to have muscle invasive bladder cancer seven years after a deceased donor renal transplantation. Nine months after radical cystectomy, a large 9 cm mass was found on his allograft, for which radical nephrectomy and excision of prior ileal conduit was performed. Pathology showed UC with sarcomatoid differentiation. Short tandem repeat (STR) genotyping confirmed donor-derived origins. Both patient tumors expressed PD-L1 suggesting an additional therapeutic avenue for these rare tumors.